Efektivitas Aturan Batas Minimal Usia Perkawinan Dalam Meminimalisir Permohonan Dispensasi Kawin Di Pengadilan Agama - Tulab, Tali (Istinbath : Jurnal Hukum, 2022)
One of the problems that never met the solution is the number of cases of underage marriage that occur in Indonesia. Even after there is a Law that regulates the minimum age of marriage is also considered to still have loopholes that can be utilized, that is, the community can still apply for marriage dispensation to the relevant Court. So this study focuses on the opinion of judges regarding the effectiveness of article 7 of Law No.16 of 2019 which determines the minimum limit that a person can hold a marriage in the Demak Class IB Religious Court. This research is a qualitative type with data search techniques through interviews with judges and documents. This study also compiled data on marriage dispensation applications before the enactment of Law No.16 of 2019 and after in the Demak Class IB Religious Court. As we know that Law No.16 of 2019 is a change from Law No.1 of 1974 on marriage which regulates the minimum age of marriage, where previously it was 19 years for men and 16 years for women then changed to 19 years for men and women. The purpose of enacting Law No.16 of 2019 is to minimize early marriage in Indonesia. But this is contrary to the data of marriage dispensation applications at the Demak Class IB Religious Court. That is, since the enactment of this regulation, the application for marriage dispensation in the Class IB Demak Religious Court has increased. This shows that this regulation is less effective in suppressing the practice of early marriage in Indonesia.